PENGARUH KEPEMIMPINAN TRANSAKSIONAL DAN TRANSFORMASIONAL TERHADAP KOMITMEN KARYAWAN PADA PT. PURNAMA GREEN LABEL SEJAHTERA DI SURABAYA - Kasiyati, Sri Budi; Yuslicha, Laiza (JEM17: Jurnal Ekonomi Manajemen, 2016)
One important factor in the life of the organization is leadership. Leadership is needed because of the existence of a specific human limitations and advantages. Effective leaders have a responsibility to always pay attention to the commitment of their subordinates because of the reality of organizational behavior at work can be measured by the level of commitment of employees. In applying the effective leadership style to be able to improve morale is high. This will have the effect positif once, either directly or indirectly to the effectiveness of the organization in achieving its goals.This study aims to: 1) determine the effect of transactional and transformational leadership simultaneously towards the commitment of employees of PT. Purnama Green Label Sejahtera Surabaya, 2) the effect of transactional and transformational leadership partially to the commitment of employees of PT. Purnama Green Label Sejahtera Surabaya, and 3) determine the dominant influence between transactional and transformational leadership variables towards the commitment of employees of PT. Purnama Green Label Sejahtera Surabaya.This study used quantitative approach by using multiple linear regression statistical analysis. Sample is taken as many as 42 employees of PT. Purnama Green Label Sejahtera Surabaya, with the result of the equation as follows: Y = 0.109 + 0,530X1 + 0,441X2 + eThe results of this study are: 1) The test results simultaneously variable transactional leadership (X1) and transformasional (X2) has a significant influence simultaneously towards the commitment of employees of PT. Purnama Green Label Sejahtera Surabaya proven true. It is evident that the value Fcount 23.876 > Ftable at 3.2381 and significance 0.000 < 0.05. Multiple determination coefficient (R2) of 0,550 or 55%. 2) partial test results that variable transactional leadership (X1) and transformational (X2) has significant influence partially to the commitment of employees of PT. Purnama Green Label Sejahtera Surabaya truth, because tcount X1 (3.389) > ttable (2.0227) and tcount X2 (3.420) > ttable (2.0227) and the significance of X1 (0,002), X2 (0.001)<0,05 , 3) variable transformational leadership (X2) is a variable that has dominant influence on the commitment of employees of PT. Purnama Green Label Sejahtera Surabaya because it has a partial determination coefficient (r2) greater than transactional leadership, which amounted to 0.2304.key word : Transactional leadership, transformational, and commitment of employees